Elżbieta Zawacka – pedagog niezłomna - Theiss, Wiesław (Pedagogika Społeczna Nova, 2021)
The article presents the socio-professional activity of Elżbieta Zawacka (1909–2009). She was an out- standing figure in the recent history of Poland. The heroine of the underground 1939–1945, participant in the Warsaw Uprising, prisoner of the Stalinist times, university professor, founder of the archival and scientific centre in Toruń. She was decorated with the Order of the White Eagle, the Cross of the Order of Virtuti Militari, and the Cross of Valor (five times). Regardless of the time, area and form of activity, Zawacka remained faithful to the “ethos of indomitables” – people acting in the name of humanistic and humanitarian values for the good of the country and other people.